Challenges and Opportunities in the Clinical Development of Immune Checkpoint Inhibitors for Hepatocellular Carcinoma. Issue 5 (12th April 2019) - Flynn, Michael J.; Sayed, Anwar A.; Sharma, Rohini; Siddique, Abdul; Pinato, David J.
Abstract : After a decade of stagnation in drug development, therapeutic reversal of immune‐exhaustion with immune checkpoint inhibitors (ICPIs) has been shown to be effective in advanced hepatocellular carcinoma (HCC). The clinical development of novel ICPIs continues at a rapid pace, with more than 50 clinical trials of immunotherapeutic agents registered as of May 2018 for this indication. The development of ICPI is particularly challenging in patients with HCC, a population with unique features which impact on safety and efficacy of immune‐modulating therapies. In this review, we discuss the biological foundations supporting the development of ICPIs across the advancing stages of HCC, focusing on the rational positioning of ICPIs across the various Barcelona‐Clinic Liver Cancer (BCLC) stages of the disease. Translational studies should guide adequate prioritization of those therapeutic agents and combination strategies which are most likely to achieve patient benefit based on solid mechanistic and clinical justifications.